Some New Classes of Topological Vector Spaces with Closed-Graph Theorems - Rodrigues, Brian (Institutional Knowledge at Singapore Management University, 1991)
In this note, we investigate non-locally-convex topological vector spaces for which the closed graph theorem holds. In doing so, we introduce new classes of topological vector spaces. Our study includes a direct extension of Ptak duality to the non-locally-convex situation.